Large-Group One-Session Treatment: A Feasibility Study of Exposure Combined With Applied Tension or Diaphragmatic Breathing in Highly Blood-Injury-Injection Fearful Individuals - Wannemueller, André; Fasbender, Alessa; Kampmann, Zarah; Weiser, Kristin; Schaumburg, Svenja; Velten, Julia; Margraf, Jürgen (Frontiers in Psychology, 2018)
Objective: Large-group one-session treatments (LG-OSTs) might represent a promising treatment tool as increasing evidence suggests their effectiveness in individuals with different situational fears. In the present study, we explored feasibility and effectiveness of an exposure-based LG-OST protocol applying applied tension and diaphragmatic breathing as coping strategies in a sample of 40 individuals, highly fearful of blood, injuries or injections (BII). Method: We assessed participants’ BII-fear using questionnaires and a behavioral approach test (BAT) before and after treatment, consisting of a blood-drawing procedure. Stability of treatment effects was assessed via online-survey at 7-month follow-up. Results: The LG-OST procedure evidenced feasible and effective. Pre-post treatment comparisons showed medium to large treatment effects (d = 0.40 – 0.93) regarding the questionnaire measures. After being treated, 70% of the individuals successfully underwent a blood drawing. Moreover, participants continued to improve in the post follow-up interval leading to large treatment effects (d = 1.19 – 1.62). Conclusions: In treating BII-fear, LG-OSTs might not only serve within a framework of a stepped care approach but also could represent a useful single-treatment option. Additionally, due to their high efficiency and standardization of treatment delivery, LG-OST protocols might foster research at the interface of basic and clinical research.